Inhibition of local hemorrhage and dermonecrosis induced by Bothrops asper snake venom: effectiveness of early in situ administration of the peptidomimetic metalloproteinase inhibitor batimastat and the chelating agent CaNa2EDTA - Rucavado Romero, Alexandra (2000)
The effectiveness of the chelating agent CaNa2EDTA and the peptidomimetic matrix metalloproteinase inhibitor batimastat (BB-94) to inhibit local tissue damage induced by Bothrops asper snake venom was studied in mice. Both compounds totally inhibited proteolytic, hemorrhagic, and dermonecrotic effects, and partially reduced edema-forming activity, when incubated with venom prior to injection. Much lower concentrations of batimastat than of CaNa2EDTA were required to inhibit these effects. In addition, batimastat, but not CaNa2EDTA, partially reduced myotoxic activity of the venom. When the inhibitors were administered at various time intervals after envenomation at the same site of venom injection, both compounds were effective in neutralizing local hemorrhage and dermonecrosis if administered rapidly after venom. Inhibition was not as effective as the time lapse between venom and inhibitor injections increased. Owing to the relevance of metalloproteinases in the pathogenesis of local tissue damage induced by B. asper and other pit viper venoms, it is suggested that administration of peptidomimetic metalloproteinase inhibitors or CaNa2EDTA at the site of venom injection may represent a useful alternative to complement antivenoms in the neutralization of venom-induced local tissue damage.